Eco-innovativebreak through: Tamarindshell-derived silver nanoparticlesforadvancedwastewaterbacterialpurification - Alaknanda J. Adur; Shilpashree Mayachar; N. Nandhini; Manjushree Mahadeva; Raajasubramanian Devarajan; Ramu Loganathan; Narendra Kuppan (Science Talks)
Access to clean drinking water remains a critical global issue, with over one billion people lacking reliable sources, as highlighted by the World Health Organization in 2005. Bacterial contamination, which leads to severe diseases like cholera and typhoid, exacerbates this challenge. Recent advancements in nanotechnology, particularly the use of silver nanoparticles (AgNPs) in water purification, offer promising solutions due to their potent antibacterial properties. This study explores the green synthesis of AgNPs utilizing tamarind shell extract as both a reducing and capping agent. The synthesized AgNPs were characterized using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), UV–Visible spectroscopy (UV–Vis), and transmission electron microscopy (TEM), revealing a crystalline structure with particle sizes ranging from 10 to 100 nm. To enhance antibacterial efficacy, these AgNPs were integrated with activated carbon, forming a composite material. This composite achieved a 90 % reduction in microbial load during wastewater treatment, effectively mitigating foul odors and discoloration. Our results demonstrate that the integration of AgNPs with activated carbon not only addresses the limitations of conventional water purification methods but also offers a cost-effective and efficient approach to bacterial contamination control. This research highlights the potential of green-synthesized AgNPs as a sustainable solution for water and wastewater management, with broader implications for public health and environmental safety.